Cementitious multiscale composite panels with vegetable fiber 3D textile reinforcement - Kohan, Lais (2024)
Textile structures present advantages to strengthen cementitious composites, which depend on the type of fiber, that are organized in bundle fiber or twisted yarn, and ligament design. In fabric-cement composites, the limited impregnation of cementitious matrix products due to thick and twisted yarns leads to premature failure due to poor bonding strength and interaction. A textile impregnated by partially biobased green-epoxy resin coating demonstrates a more cohesive behavior, ensuring even stress distribution throughout the yarns. To guarantee the mechanical properties of composite, good adhesion between textile-matrix is necessary, besides avoiding fiber degradation. The use of hybrid braids can reduce costs and increase efficiency. This study assessed how two commercial jute textiles and 2D or 3D sisal/PET hybrid braided textiles, separately, affect the interactions by reinforcement of cementitious composites, these interactions were assessed according to mechanical behavior (four-point bending, tensile stress, and physical fabric characteristics), bonding and interfacial transition zone (pullout test, flexural stress specific deformation behavior, scanning electron microscopy - SEM), and visual and chemical compounds analysis (X-ray diffraction - XRD, Fourier Transform Infrared Spectroscopy, energy-dispersive X-ray spectrometer - EDS). The open weave jute fabric exhibited inferior mechanical properties (tensile behavior - 175 N and mass per area 192 g/m²). However, its larger interstices in the weave structure played a superior interaction with the matrix in composite boards, and micro silica coating displayed an enhanced ultimate strength modulus of rupture (6.81 MPa), and the highest specific energy (4.28 ± 0.91) kJ/m². The calcium-silicate-hydrate products are responsible for strong chemical adhesions between the phases of the composite. Among developed sisal/PET braided textiles, due to green epoxy resin being stiffer, comparing sisal/PET yarn before and after coating, the youngs modulus doubled its value (from 2.12 ± 0.32 to 4.11 ± 0.36 N/Tex). Sisal/PET yarn presented in the pullout test of yarn-mortar the pseudo-ductile behavior and high energy absorption, the peak load (371.26 N), and toughness until peak loading (2110.00 N.mm). Composites reinforced by multidimensions textiles exhibited 3D fabric superior values than 2D textiles in four-point bending tests for modulus of rupture (7.45±0.48 MPa) and specific energy (5.72±0.31 kJ/m²). Finally, textile treatments, inorganic powder coatings, and resin coating on textile are necessary for its application to ensure even stress distribution throughout the yarns into interface transition between textile-cementitious, and enhanced tensile strain capacity of composites.